Bioaccumulation of mercury by the panaeid prawns from Rushikulya estuary, east coast of India - Das, Snehalata (Indian Journal of Fisheries, 2011)
Commercially important penaeid prawns namely Penaeus monodon and Penaeus indicus from the waters of a tropical estuary along the east coast of India were exposed for 96 hours down to different concentrations of HgCl^ at various salinities. The accumulation patterns of mercury were analysed at 24-hour interval with respect to concentrations of 0.005 and 0.01 ppm and salinities of 5, 15 and 25 psu in various body parts such as digestive tract, exoskeleton and muscle of the organisms. The highest concentrations of mercury was observed in the digestive tract compared to other body parts and the order of accumulation was found to be as digestive tract > exoskeleton > muscle with increase in concentrations and time period for both the species. At salinity of 15 psu Hg content was highest while 25 psu was the lower than 15 psu but higher than 5 psu salinity indicating 15 psu salinity as a favourable medium for Hg accumulation in each case. P. monodon was noticed to be more sensitive indicator organism than P. indicus